The Relationship between the Existence of Butler and Service Quality received by VIP Guests - Fandya, Nevie Ariesa; Nurbaeti, Nurbaeti; Sulartiningrum, Sri (Institut Pariwisata Trisakti, 2017)
Good service quality in the hotel can be achieved if employees are able to anticipate and meet the guest’s needs. Therefore, it is necessary to have a section focusing on a certain type of guests, namely VIP and VVIP guests. in order to achieve good relations with guests. This section is called Butler which cover personal services so that the service quality is expected to increase. This study aims to study the guests opinion about the existence of Butler at Raffles Hotel, Jakarta and to find out the relationships between Butler and service quality. Research methods used is descriptive correlational where correlational coefficient and coefficient of determination are computed. Data was collected using questionnaire distributed to VIP/VVIP guests at Raffles Hotel Jakarta. Sample size was 53 and sampling technique was non probability purposive sampling. The result showed that on the whole the existence of butler was rated very good by VIP guests in Raffles Hotel Jakarta. Meanwhile, service quality received by guests was also very good. There was a strong positive relationship between Butler's existence and service quality in Raffles Hotel Jakarta.